3D Cell Culture Models Demonstrate a Role for FGF and WNT Signaling in Regulation of Lung Epithelial Cell Fate and Morphogenesis - Rabata, Anas; Fedr, Radek; Soucek, Karel; Hampl, Ales; Koledova, Zuzana (Frontiers in Cell and Developmental Biology, 2020)
FGF signaling plays an essential role in lung development, homeostasis, and regeneration. We employed mouse 3D cell culture models and imaging to study ex vivo the role of FGF ligands and the interplay of FGF signaling with epithelial growth factor (EGF) and WNT signaling pathways in lung epithelial morphogenesis and differentiation. In non-adherent conditions, FGF signaling promoted formation of lungospheres from lung epithelial stem/progenitor cells (LSPCs). Ultrastructural and immunohistochemical analyses showed that LSPCs produced more differentiated lung cell progeny. In 3D extracellular matrix, FGF2, FGF7, FGF9, and FGF10 promoted lung organoid formation. FGF9 showed reduced capacity to promote lung organoid formation, suggesting that FGF9 has a reduced ability to sustain LSPCs survival and/or initial divisions. FGF7 and FGF10 produced bigger organoids and induced organoid branching with higher frequency than FGF2 or FGF9. Higher FGF concentration and/or the use of FGF2 with increased stability and affinity to FGF receptors both increased lung organoid and lungosphere formation efficiency, respectively, suggesting that the level of FGF signaling is a crucial driver of LSPC survival and differentiation, and also lung epithelial morphogenesis. EGF signaling played a supportive but nonessential role in FGF-induced lung organoid formation. Analysis of tissue architecture and cell type composition confirmed that the lung organoids contained alveolar-like regions with cells expressing alveolar type I and type II cell markers, as well as airway-like structures with club cells and ciliated cells. FGF ligands showed differences in promoting distinct lung epithelial cell types. FGF9 was a potent inducer of more proximal cell types, including ciliated and basal cells. FGF7 and FGF10 directed the differentiation towards distal lung lineages. WNT signaling enhanced the efficiency of lung organoid formation, but in the absence of FGF10 signaling, the organoids displayed limited branching and less differentiated phenotype. In summary, we present lung 3D cell culture models as useful tools to study the role and interplay of signaling pathways in postnatal lung development and homeostasis and we reveal distinct roles for FGF ligands in regulation of mouse lung morphogenesis and differentiation ex vivo.